2005
DOI: 10.4028/www.scientific.net/msf.488-489.535
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Grain Size on Ductility of AZ31 Magnesium Alloy

Abstract: It is well known that the ductility of magnesium and magnesium alloy is too poor to be processed. After normal hot extrusion, the ductility of magnesium alloy will be improved, but not noticeably. In this paper, further extrusion (Extrusion Ratio is 6.25) is adopted to commercial AZ31 magnesium alloy rods (Extrusion Ratio is 2) at different temperatures in order to refine the size of grain, then the rods with the crystallite size between 4-10μm is obtained, and the influence of crystallite with different grain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 7 publications
1
10
0
Order By: Relevance
“…2); and (d) the redistribution of basal plane (0 0 0 1) in the case of nano-composite samples. Grain refinement particularly benefits hexagonal metals in ductility increment [7,23]. In earlier studies Wang et al revealed an increase in ductility up to 30.82% by reducing the grain size to below 5 m. These results are consistent in principle with the results obtained in our study (see Tables 1 and 3).…”
Section: Mechanical Behaviorsupporting
confidence: 95%
See 1 more Smart Citation
“…2); and (d) the redistribution of basal plane (0 0 0 1) in the case of nano-composite samples. Grain refinement particularly benefits hexagonal metals in ductility increment [7,23]. In earlier studies Wang et al revealed an increase in ductility up to 30.82% by reducing the grain size to below 5 m. These results are consistent in principle with the results obtained in our study (see Tables 1 and 3).…”
Section: Mechanical Behaviorsupporting
confidence: 95%
“…This observation is not unique as ductility improvement in AZ31B was also attempted using addition of Mn [11] and Sr [21] and Li [22]. The increase in ductility of AZ31B/Al 2 O 3 formulations can primarily be attributed to: (a) grain refinement [23]; (b) presence and reasonably good distribution of Al 2 O 3 particulates [2]; (c) reduction in size and roundness of second phase (see Table 2 and Fig. 2); and (d) the redistribution of basal plane (0 0 0 1) in the case of nano-composite samples.…”
Section: Mechanical Behaviormentioning
confidence: 80%
“…[5][6][7] The effect of fine grain size on the ductility of magnesium at room temperature has been observed since the 1960s. [8][9][10][11][12] Observations on coarse-grained material demonstrate an abrupt change in ductility at around 230 C (Fig. 1), while fine-grained structure smoothes out this inflexion.…”
Section: Introductionmentioning
confidence: 95%
“…This is a commercial magnesium alloy with wide application in the automotive and aerospace industries. It should be mentioned that so far, the studies that have been conducted on the effect of grain size on the mechanical behavior of AZ31B magnesium alloys have been focused on the low strain rate conditions [11][12][13][14][15][16][17][18][19][20][21][22]. Besides, in the available reports in the literature on the high strain-rate deformation of AZ31B alloys [23][24][25][26][27][28][29][30], the effect of grain size is not investigated and there is a considerable knowledge gap in the correlation between the grain size and dynamic impact response of AZ31B magnesium alloys.…”
Section: Introductionmentioning
confidence: 99%